Changes in sediment connectivity and its impact on sediment transport in a typical watershed of Southern Jiangxi Province, China - Fei Sheng; Tingxin Yi; Yanyan Wang; Haijin Zheng; Shiyu Liu; Xiaofei Nie; Longsong Hu; Haifeng Li (Ecological Indicators)
Sediment connectivity is a crucial factor in determining the mode, efficiency, and scale of sediment transport. However, changes in sediment connectivity and their impact on sediment transport in southern Jiangxi Province, China, remain unclear. Consequently, the Lianshui watershed in southern Jiangxi Province was selected as the study area for this research. Using hydrometeorological and land use data from 1992 to 2023, this study examines variations in sediment connectivity and sediment transport eigenvalues within the watershed. It also investigates the hysteresis relationship between runoff and sediment under single rainstorm conditions and assesses the impact of changes in sediment connectivity on sediment transport. The findings revealed that the mean index of sediment connectivity (ICmean) in the watershed from 1992 to 2023 exhibited a highly significant upward trend. The ICmean for each land use type increased significantly, with the ICmean for other woodland changing dramatically. The hotspot area of the index of sediment connectivity (IC) showed significant spatial expansion. The annual sediment yield (S), sediment yield modulus (SSY), sediment yield coefficient (Cs), 3-year and 5-year moving average sediment yield (S3a, S5a) all increased significantly from 1992 to 2023. Under single rainstorm conditions, the proportion of each runoff-sediment loop curve varied greatly across different periods. The highest proportion of counterclockwise and figure-eight curves was found during the periods 2001–2008 and 2009–2023, at 35.3% and 54.0%, respectively. These changes were closely related to the location and quantity of sediment sources caused by the large-scale development of orchards in the watershed. The interpretation of ICmax to the changes in S3a and S5a was 51.5%, indicating a highly significant effect. This suggests that alterations in sediment connectivity play a crucial role in sediment transport processes. The research results provide a scientific basis for controlling soil erosion and optimizing land use allocation in the watershed.